KOMBINASI INTEGRATED NEUROMUSCULAR INHIBITION TECHNIQUE DENGAN ULTRASOUND LEBIH EFEKTIF DALAM MENURUNKAN RASA NYERI DIBANDINGKAN KOMBINASI STRAIN COUNTERSTRAIN DENGAN ULTRASOUND PADA PENDERITA PIRIFORMIS SYNDROME - I Nyoman Baktiyasa; Ari Wibawa; I Putu Adiartha Griadhi (Bachelor of Physiotherapy and Physiotherapy Profession Study Program, Faculty of Medicine, Udayana University in collaboration with Indonesian Physiotherapy Association (IPA), 2017)
ABSTRACTPiriformis Syndrome is a collection of symptoms such as pain, tingling or numbness from the buttocks down to thefoot. In this condition, patients can be given intervention with Integrated Neuromuscular Inhibition Technique, StrainCounterstrain and Ultrasound. With Paired Sample t-test on Group 1 that got the value of p =0.000 with mean differences2.940±0.96,while at Group 2 that got the value of p=0.000 with mean differences 1.910±0.60. In test of differencebetween Group 1 and Group 2 using Independent Sample t-test showed p=0,010 (p<0,05). These researchshowed that combination of Integrated Neuromuscular Inhibition Technique with Ultrasound is more effective in relievingpain than combination of Counterstrain Strain with Ultrasound in Piriformis Syndrome.Keyword: Integrated Neuromuscular Inhibition Technique, Strain Counterstrain, Ultrasound, Piriformis Syndrome